Chikungunya resurgence in the Maldives and risk for importation via tourists to Europe in 2019–2020: A GeoSentinel case series. Issue 36 (July 2020) - Dudouet, Pierre; Gautret, Philippe; Larsen, Carsten Schade; Díaz-Menéndez, Marta; Trigo, Elena; von Sonnenburg, Frank; Gobbi, Federico; Grobusch, Martin P.; Malvy, Denis; Field, Vanessa; Asgeirsson, Hilmir; Souto, Inés Oliveira; et al.
Abstract: Background: Chikungunya virus (CHIKV) is an arthropod-borne virus mainly transmitted in tropical areas by Aedes spp. mosquitoes. It has been responsible for small-to-large outbreaks in temperate areas including southern Europe and North America. Past outbreaks in 2006 on the islands of Maldives, as well as on other islands in the Indian Ocean and in Southeast Asia, demonstrated for the first time the capacity of CHIKV to disseminate through travel and transcontinental commerce, and revealed the major socio-economic impact of CHIKV epidemics. Recently, CHIKV has been circulating in highly touristic areas including the Maldives, where 1736 cases were notified by the Health Protection Agency during 2019. Case series: Among EuroTravNet/GeoSentinel patient records, eight CHIKV-confirmed cases imported the Maldives to France, Germany, Denmark, Italy and Spain were identified between February 2019 and February 2020; exceeding the total number of CHIKV infections travel-acquired in Maldives reported to this surveillance network during the previous 10 years. Conclusions: The prevention and control of CHIKV introduction into naïve areas colonised by competent vectors is crucial. CHIKV outbreaks must be detected and reported in a timely manner. This must lead to adapted health information for international travellers and to prompt management of suspected imported cases. Conversely, travellers make for excellent sentinels and increased reports of imported cases might reflect a change in the level of endemicity or even herald an outbreak. Feedback to the local health authorities and matching this with local epidemiological surveillance data may lead to health benefits for the local population.